PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, CAPITAL INTENSITY RATIO DAN KOMISARIS INDEPENDEN TERHADAP EFFECTIVE TAX RATE (Study Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2014-2016) - Ratih Widyawati, 13.05.52.0006; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2017)
This study aims to analyze the effect of firm size, leverage, profitability, capital intensity ratio and independent commissioner to effective tax rate. In this study popuation are used companies registered in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2016 . The sampling technique using purposive sampling. Mechanical testing data is to use a multipe linear regression analysis. The analysis showed that the variables firm size, capital intensity ratio, indepentdent commissioner had no effect on effective tax rate. Leverage and profitability had effect on effective tax rate.Keywords: Firm Size, Leverage, Profitability, Capital Intensity Ratio and Independent Commissioner, Rate.Effective Tax